Proposta de um instrumento de medida para mensurar a motivação de servidores públicos - Flôres, Fernanda Dalcin (2019)
The world of work has undergone many changes in recent years due to the technological advances and demands of globalization, leading organizations to seek more and more subsidies and information about their human resources. In this context, the general objective of this study was to propose a measurement instrument that allows to measure the motivation of federal public servants based on the Theory of Response to the Item. The methodological procedures adopted characterize the research as descriptive, exploratory and quantitative. The target population was the upper level administrative technicians, class E, of the Federal University of Santa Maria and the instrument used for data collection was a questionnaire. For the analysis of the results, the classical analysis using the SPSS and TESTFACT software was used to analyze the reliability and the unidimensionality of the motivation construct, and later the items were analyzed in the BILOG-MG software from the application of the Logistic Model of 2 Parameters (ML2) of the Item Response Theory to verify the internal consistency and the estimation of the parameters of difficulty and discrimination of the item. The final result of the application of the systematics was the construction of a measuring instrument capable of measuring the motivation of public servants. With the results of the survey, managers can analyze and plan how best to manage their human resources, especially their administrative staff.